Waterpipe-specific pictorial health warning labels are effective in reducing subjective measures, behavioral responses and toxicant exposure among young adults: A crossover study - Natasha Shaukat; Sreshtha Chowdhury; Simanta Roy; Taghrid Asfar; Zoran Bursac; Wasim Maziak (PLoS ONE, 2025)
Background This study aims to assess the impact of six evidence-based Waterpipe (WP)-specific pictorial health warnings (HWs) placed on the WP device on puffing behavior, toxicant exposure, subjective smoking experiences, harm perception, motivation and intention to quit among young WP smokers in Florida. Methods In a crossover experiment, a total of 100 WP smokers completed two 45-minute ad-libitum WP smoking sessions (without HW vs. with HW on the device) after a 12-hour abstinence. Exhaled Carbon Monoxide (eCO) was measured before and after each session, while puff topography was recorded throughout the smoking session. Additionally, participants completed survey questionnaires before and after the WP smoking sessions to assess subjective smoking experiences, harm perception, motivation to quit, and intention to quit. Results Study participants had a mean age of 22.5 years (SD = 3.4), and most (56.6%) were male.The mean e-CO boost (34.16 vs. 26.58) (p = 0.006) was higher in the no-HW condition compared to the HW condition. Differences were also observed between the two conditions for puff topography. For example, median smoking time (46.4 min vs 45.3 min; p < 0.001), median puffing time (4.35 min vs. 4.22 min; 0.004), average puff duration (3.13 sec vs. 2.90 sec; 0.029), and the total number of puffs (95.0 vs. 84.0; 0.039) were lower in the HW compared to no-HW conditions. Subjective measures also demonstrated differences between the two conditions, including greater suppression of the urge to smoke (14.98 vs. 7.51; p < 0.001), reduced puff liking (4.01 vs. 3.63; p = 0.010), and reduced puff satisfaction (4.11 vs. 3.65; p = 0.009) following exposure to HW compared to no-HW conditions. Motivation to quit (p = 0.058), intention to quit (p = 0.659), and harm perception (p = 0.301) increased after smoking the WP with HW; however these were not statistically significant. Conclusion Using an evidence-based approach, a large sample size for clinical studies, and an efficient and sensitive within-subject design, this study demonstrates that pictorial HWs on WP devices effectively reduce smoking behavior, toxicant exposure, and subjective experiences while increasing harm perception, intention, and motivation to quit WP smoking.